Emilia-Romagna water protection plan and climate change - Draghetti T.; Bortone G. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The climate change is in action, and it will accompany us in the future. It will have a significant impact on the water cycle and the water management. In spite of many forecasting models and many evolutionary scenarios, the uncertainty about data and projections is still remarkable. It will be necessary to reduce the vulnerability of the civil society by moving towards the protection and recovery of the natural ability of the ecosystems on the mitigation of the effects. Moreover it is necessary that the policy and the actions on the water management and protection be elaborated with the participation of all stakeholders. The Water Protection Plan of the Emilia-Romagna Region has an approach to water resources planning mainly based on the sustainable development, and it seeks the water efficient use and the water saving and conservation.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)